Integrated Cooperative Learning Model of Local Wisdom Values on Mastery of Science Concepts - Ripo, Delsi; Latjompoh, Masra; Odja, Abdul Haris; Uloli, Ritin; Payu, Citron S.; Hermanto, I Made (Jurnal Pijar Mipa, 2025)
Learning models are guidelines for educators in planning classroom learning, starting from preparing tools, media and learning instruments, to assessment tools that lead to efforts to achieve learning objectives. This study aims to test the effect of implementing integrated cooperative learning media with local wisdom values on the mastery of science concepts at SMPN 2 Telaga Biru. The research design used is a One-Shot Case Study Design, and this study uses two classes as samples. The data analysis techniques used are the normality test and the hypothesis test. Cognitive learning outcomes through hypothesis testing criteria, where the experimental class has a t-count value of 11.19, and the replication class has a t-count value of 15.36. While the t-table value in the experimental class and replication class is 2.07. From the results of data testing, the t-count value ≥ t-table with a level of ∝ = 0.05 for the two classes, it can be concluded that H0 is rejected and H1 is accepted.   The results of the study showed a significant increase in concept mastery after the implementation of the cooperative learning model. The implementation of the cooperative learning model can change the pattern of student interaction for the better because it contains steps and designs. Data analysis showed that the average posttest score was higher than the KKTP score. This study concludes that the implementation of the cooperative learning model can be an effective alternative to improve mastery of science concepts.